COVID-19 Pandemic and Economic Inequalities: Analysis of the Discourses of Turkish Political Parties on Twitter - Şen, Ayşe Fulya (Taylor and Francis, 2023)
This study analyzed the political discourses of the political parties on current economic issues intensifying during the COVID-19 period and discussed the limitations and capacities of the political discourses and Twitter as a public sphere. The aim of this essay is to analyze the political parties’ discourses on economic inequality on Twitter during the COVID-19 process. In such context, while it was expected, the main opposition party highlighted the economic crisis and inequality with its economic and political consequences, it also contented by criticizing the ruling party within populist rhetoric over inflation and price increase. On the other hand, it was seen that the ruling party, AK Party, only focused on increasing the minimum wage and did not reference the issues stemming from the capitalist economy. Although the two political parties also dealt with poverty-reduction efforts, it can also be said there was no disagreement on the idea of the free market and the naturalization of economic inequalities. This research reveals that there existed a “significant silence” on economic inequality in the political discourse. © 2024 selection and editorial matter, Vikas Kumar and Mohit Rewari; individual chapters, the contributors.